Treatment of Menopausal Hot Flashes with 5-Hydroxytryptophan - Freedman, Robert R. (2009)
OBJECTIVE: Much recent research has focused on nonhormonal treatments for menopausal hot flashes. The purpose of the present study was to determine the effects of 5-Hydroxytroptophan (5-HTP), the immediate precursor of serotonin, upon menopausal hot flashes. Selective, serotonergic, reuptake inhibitors (SSRI’s), which increase the amount of serotonin in the synaptic gap, have shown some promise in the amelioration of hot flashes. METHODS: We administered 5-HTP or placebo, in double-blind fashion, to 24 postmenopausal women reporting frequent hot flashes. Treatment outcome was measured using a miniature, electronic, hot flash recorder. RESULTS: No significant effects of 150 mg/day 5-HTP upon hot flash frequency were found. The 5-HTP group had 23.8 ± 5.7 (SD) hot flashes/24 hours prior to treatment and 18.5 ± 9.6 at the end of treatment. The placebo group had 18.5 ± 9.6 before treatment and 22.6 ± 12.4 at treatment completion. CONCLUSIONS: At the dose given, 5-HTP does not significantly ameliorate frequency of menopausal hot flashes, as measured objectively with an electronic recorder. Given the small size, this study must be considered preliminary in nature.